Oxylipins Associated to Current Diseases Detected for the First Time in the Oxidation of Corn Oil as a Model System of Oils Rich in Omega-6 Polyunsaturated Groups. A Global, Broad and in-Depth Study by 1H NMR Spectroscopy - Jon Alberdi-Cedeño; María L. Ibargoitia; María D. Guillén (MDPI AG, 2020)
For the first time, an important number of oxylipins have been identified and quantified in corn oil submitted to mild oxidative conditions at each time of their oxidation process. This oil can be considered as a model system of edible oils rich in polyunsaturated omega-6 groups. The study was carried out using 1H nuclear magnetic resonance spectroscopy (1H NMR), which does not require chemical modification of the sample. These newly detected oxylipins include dihydroperoxy-non-conjugated-dienes, hydroperoxy-epoxy-, hydroxy-epoxy- and keto-epoxy-monoenes as well as E-epoxy-monoenes, some of which have been associated with several diseases. Furthermore, the formation of other functional groups such as poly-formates, poly-hydroxy and poly-ether groups has also been proven. These are responsible for the polymerization and increased viscosity of the oil. Simultaneously, monitoring of the formation of well-known oxylipins, such as hydroperoxy-, hydroxy-, and keto-dienes, and of different kinds of oxygenated-alpha,beta-unsaturated aldehydes such as 4-hydroperoxy-, 4-hydroxy-, 4-oxo-2E-nonenal and 4,5-epoxy-2E-decenal, which are also related to different degenerative diseases, has been carried out. The provided data regarding the compounds identification and their sequence and kinetics of formation constitute valuable information for future studies in which lipid oxidation is involved, both in food and in other scientific fields.